Echoes of the “Keraton”: Translating Javanese Court Culture for local and Global Viewers - Asmarani, Rahmanti; Bayu Ade Prabowo; Sri Oemiati (Universitas Sulawesi Barat, 2025)
This study analyzes translation strategies employed in subtitling the